Online Learning Management Difficulties: Higher Education Students Perspective - Syathroh, Isry Laila; Syarifudin, Achmad; Judijanto, Loso; Mubin, Minahul; Sanulita, Henny (Journal of Education Technology, 2024)
Implementing an online-based learning management system, educators must prepare materials and other learning tools such as lesson implementation plans. But the fact is that 57% of students have difficulty when online learning is carried out. The research aims to analyze the process of implementing online learning carried out in universities using online media. This research is urgently carried out because there are differences between theory and reality in the field. The research method used was a mixed method with surveys and interviews with students. The subjects in this research were 150 university students from all study programs who were chosen randomly. Data collection techniques using surveys by distributing instruments to students. The instrument was prepared and developed and has been validated. The instrument was given a score on a Likert scale starting from point 1 to point 5. Data was also obtained by interviewing 10 students who were randomly selected from 150 survey respondents. The data analysis technique uses SPSS Version 26. Data is analyzed by calculating the average of each indicator and making it in the form of a bar chart. Interviews were analyzed by collecting data, reducing data, and drawing conclusions. As a result, it was found that students had difficulties in the online learning process. Difficulties arise because of the obstacles experienced by lecturers when implementing learning. The impact of these obstacles affects the learning process and reduces students' understanding and knowledge.